Improving Mathematical Problem-Solving Ability Through Problem-Based Learning (PBL) Model Using Augmented Reality Media - Okta, Ira Maya; Fathani, Abdul Halim; Sari, Fadhila Kartika (Universitas Teknokrat Indonesia, 2025)
The research aims to improve students’ Mathematical Problem-Solving Ability (KPMM) by applying the Problem-Based Learning (PBL) model assisted by Augmented Reality media. This research was a collaborative or participatory classroom action research and involved researchers, mathematics educators, colleagues, and students in grade IX of SMP Islam Muallimin Kediri in the even semester of the 2023/2024 academic year. The research instruments consisted of learning devices and data collection instruments. The learning devices employed the Lesson Implementation Plan (RPP), Student Worksheets (LKPD), and AR-Build Space Media. Meanwhile, data collection instruments were observation sheets, interviews, and KPMM tests. Data analysis was conducted descriptively comparatively. The results indicated that implementing the Problem-Based Learning (PBL) model assisted by Augmented Reality media significantly increased students’ KPMM, with the average class value increasing from 56.75 in cycle I to 73.87 in cycle II. In short, the implementation of the PBL model assisted by augmented reality media could increase the KPMM of SMP Islam Muallimin Kediri’s students in grade IX.